Farmers, Hunters, and Colonists Interaction Between the Southwest and the Southern Plains - Spielmann, Katherine A. (University of Arizona Press, 1991)
Eight contributors discuss early trade relations between Plains and Pueblo farmers, the evolution of interdependence between Plains hunter-gatherers and Pueblo farmers between 1450 and 1700, and the later comanchero trade between Hispanic New Mexicans and the Plains Comanche.